Answers

2014-08-18T21:01:14+05:30
I will be using A, B, C not angle A or angle B.... Hope you will not mind it.

As we know A + B + C = 180
So, B + C = 180 - A
Or, (B/2) + (C/2) = 90 - (A/2) ....(1)

Now think in triangle BOC,
we have three angles, OBC, BOC and OCB
OBC = (B/2)
OCB = (C/2)
Let BOC = X

So, X + (B/2) + (C/2) = 180
From equation (1)

X + 90 - (A/2) = 180
X = 90 + A/2  (Proved !!!)
2 2 2
thanks so much my test is tomarrow so thanx lot
2014-08-18T21:08:25+05:30
A + b+c = 180
b/2 + c/2 = 180 - a/2 - 1....

obc = b/2 
ocb = c/2
boc =x

X + b/2 + c/2 = 180

x+ 180 - a/2 = 180
x = 90 + boc

0
thanx lot............................